Variasi Morfometrik dan Pengelompokan Spesies Kantong Semar (Nepenthes Spp.) di Desa Simpang Kasturi Kecamatan Mandor - Riza Linda, Anastasia Selviana, Masnur Turnip, (Jurnal Protobiont, 2018)
Nepenthes spp. is one of the ornamental plants in Indonesia that has much uniquenesses on its pitcher cup in shape and colour. The purpose of this research is to recognize the variety of morphometric characters and to know the grouping of Kantong Semar species (Nepenthes spp.) in Simpang Kasturi Village, Mandor District. The study was conducted for 3 months from October to December 2017 at Simpang Kasturi Village Forest, Mandor District. Identification, data processing, and the making of herbarium were done in Biology Laboratory of Biology Department, Mathematics and Natural Science Faculty of Tanjungpura University, Pontianak. The research method was done using the survey method following by sampling processes performed by taking samples of leaves, stems, and pitcher cup. Samples then were observed based on morphological characteristics of leaves, tendrils, stems and pitcher cup. Furthermore, collected data were analyzed using cluster analysis (grouping analysis) with SPSS 21 program. The results of this study found 5 individuals from 4 species of Nepenthes which have different morphometric characters among themselves. The most various morphological character among the species is the morphological character of the pitcher cup. Nepenthes rafflesiana has the largest pitcher cup size while Nepenthes gracilis has the smallest one size. Based on the coefficient value, the most significant grouping is Nepenthes rafflesiana with Nepenthes mirabilis, while the closest one is Nepenthes ampullaria 1 with Nepenthes ampullaria 2.